Effect of Reynolds Number and Property Variation on Fluid Flow and Heat Transfer in the Entrance Region of a Turbine Blade Internal-Cooling Channel - Ben-Mansour R.; Al-Hadhrami L. (International Journal of Rotating Machinery)
Internal cooling is one of the effective techniques to cool turbine blades from inside. This internal cooling is achieved by pumping a relatively cold fluid through the internal-cooling channels. These channels are fed through short channels placed at the root of the turbine blade, usually called entrance region channels. The entrance region at the root of the turbine blade usually has a different geometry than the internal-cooling channel of the blade. This study investigates numerically the fluid flow and heat transfer in one-pass smooth isothermally heated channel using the RNG k−ϵ model. The effect of Reynolds number on the flow and heat transfer characteristics has been studied for two mass flow rate ratios ( 1/1 and 1/2 ) for the same cooling channel. The Reynolds number was varied between 10 000 and 50 000 . The study has shown that the cooling channel goes through hydrodynamic and thermal development which necessitates a detailed flow and heat transfer study to evaluate the pressure drop and heat transfer rates. For the case of unbalanced mass flow rate ratio, a maximum difference of 8.9 % in the heat transfer rate between the top and bottom surfaces occurs at Re=10 000 while the total heat transfer rate from both surfaces is the same for the balanced mass flow rate case. The effect of temperature-dependent property variation showed a small change in the heat transfer rates when all properties were allowed to vary with temperature. However, individual effects can be significant such as the effect of density variation, which resulted in as much as 9.6 % reduction in the heat transfer rate.